Midazolam을 사용한 의식하 진정 내시경에서 Flumazenil의 투여가 회복시간 및 내시경 만족도에 미치는 영향 - 김대겸; Dae Kyoum Kim; 정훈용; Hwoon Yong Jung; 고효미; Hyo Mi Ko; 조지윤; Ji Yun Jo; 김석균; Seog Gyun Kim; 이돈; Don Lee; et al. (Taehan Sohwagi Naesigyŏng Hakhoe chi, 2008)
목적: Midazolam을 사용한 내시경 검사 후 flumazenil의 사용은 일상 생활로의 안전하고 빠른 복귀를 가능하게 할 것으로 기대되나 적정 사용량에 대한 연구가 부족한 실정이다. Flumazenil의 용량에 따른 의식회복과 퇴원시간의 단축여부, 내시경 만족도 및 퇴원 후 기억소실에 미치는 영향을 규명하여 적정한 사용량 선택에 도움을 주고자 하였다. 대상 및 방법: 2006년 9월부터 11월까지 서울아산병원 건강증진센터에서 내시경 검사를 시행 받은 18세 이상의 성인 남녀 150명을 대상으로 하였다. 수검자를 세 군으로 무작위 배정하여 midazolam을 사용한 의식하 진정 내시경을 시행하고 검사 종료 10분 후에 각각 생리식염수, flumazenil 0.25mg, flumazenil 0.5 mg을 투여한 뒤 의식회복시간, 퇴원시간, 검사 만족도를 측정하여 비교하였다. 퇴원 후 발생한 기억소실 여부를 검사 종료 24시간 후 전화 설문으로 조사하여 비교하였다. 결과: 세 군간에 연령, 성별, 체중, 알코올 소비량, 사용된 midazolam의 용량에는 차이가 없었다. 검사 종료 후 의식회복시간은 flumazenil 사용 군에서 의미 있게 단축되었다(28.5±15.0분, 13.8±3.7분, 12.4±1.7분). 퇴원시간은 flumazenil 사용군에서, flumzenil 0.25 mg 사용 군 보다는 0.5 mg 사용 군에서 의미 있게 단축되었다(41.2±20.5분, 22.1±10.9분, 16.4±2.2분)(p＜0.001). 퇴원 시 암기사항을 다음날 얼마나 기억하고 있는지 전화 설문으로 확인하였을 때 각각 45.5%, 30.4%, 8.9%가 전혀 기억을 하지 못하였다. 하지만 수검자의 검사 만족도는 세 군간에 차이를 보이지 않았다. 결론: Midazolam을 사용한 내시경에서 flumazenil의 사용은 의식회복시간과 퇴원시간을 의미 있게 단축시키며 퇴원 후 기억소실을 감소시켜 안전하고 빠른 일상 생활로의 복귀에 도움을 줄 것으로 기대한다. Background/Aims: Treatment with flumazenil results in rapid reversal from sedation. In addition, the use of flumazenil can prevent accidents or memory loss after endoscopy. This study was conducted to evaluate the role of flumazenil according to dose. Methods: A total of 150 consecutive outpatients were randomly allocated into three groups: patients given normal saline (control group), patients given 0.25 mg flumazenil (0.25 mg flumazenil group) and patients given 0.5 mg flumazenil (0.5 mg flumazenil group). Flumazenil or normal saline was injected 10 minutes after the completion of endoscopy. We evaluated the recovery time, time to discharge, patient satisfaction, and memory loss after discharge. Results: The control group consisted of 44 subjects, the 0.25 mg flumazenil group consisted of 46 subjects and the 0.5 mg flumazenil group consisted of 45 subjects. The recovery time was significantly shorter in the two flumazenil groups as compared to the control group (28.5±15.0 min, 13.8±3.7min, 12.4±1.7 min for the control group, 0.25 mg flumazenil group and 0.5 mg flumazenil group, respectively)(p＜0.001). The time to discharge after an examination was shorter in the flumazenil groups and showed dose-dependency (41.2±20.5 min, 22.1±10.9 min, 16.4±2.2 min for the control group, 0.25 mg flumazenil group and 0.5 mg flumazenil group, respectively) (p＜0.001). There was no significant difference in patient satisfaction among the three groups. The degree of memory recall was better in the 0.5 mg flumazenil group than in the other two groups p＜0.001). Conclusions: Flumazenil reversal of midazolam sedative endoscopy results in fast recovery and is helpful to minimize memory loss after an examination without interference of satisfaction. (Korean J Gastrointest Endosc 2008;36:206-212)